2021
DOI: 10.1093/jas/skab079
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of prolactin promotes secondary skin follicle activation in cashmere goats

Abstract: The aim of this study was to investigate the involvement of prolactin (PRL) on development of secondary skin follicles in cashmere goats. Goats were randomly assigned to either a bromocriptine treatment or control group. Samples of cashmere fiber, blood and skin were collected from all goats after 1 month. The results indicated that the length, growth rate and diameter of fibers were not influenced (P > 0.05) by the inhibition of prolactin resulting from the treatment with bromocriptine. There was a ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 53 publications
0
9
0
1
Order By: Relevance
“…The cashmere quality at 1 year old is the highest among all age groups, and with the increase in age, the cashmere quality had a decreasing trend. Some reports show that low energy and protein levels can improve the fineness and length of cashmere, trace elements can improve the strength of cashmere fiber, and the change in blood hormone levels will affect the character of cashmere [ 34 , 35 ]. The quality is highest in 1/2-year-old goats and thereafter declines with the increasing age of the animals [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cashmere quality at 1 year old is the highest among all age groups, and with the increase in age, the cashmere quality had a decreasing trend. Some reports show that low energy and protein levels can improve the fineness and length of cashmere, trace elements can improve the strength of cashmere fiber, and the change in blood hormone levels will affect the character of cashmere [ 34 , 35 ]. The quality is highest in 1/2-year-old goats and thereafter declines with the increasing age of the animals [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Shamsalddini et al [85] showed that the CC genotype had the longest fibers compared to the AA and AC genotypes (p < 0,05), while there was no significant association between the PRL gene genotypes and fiber diameter. These results imply that the PRL gene polymorphism can be used as a molecular marker to improve fiber formation without adversely affecting fiber diameter [82,84,86]. In the POU1F1 gene, a positive regulator for PRL, a polymorphism at 3' UTR was identified as a putative molecular marker for senior cashmere yield [100].…”
Section: Candidate Genesmentioning
confidence: 93%
“…The distinct regulation of primary and secondary HF morphogenesis and cycling has been shown in mice and Cashmere goat. 35,155 Depending on the factors that are deregulated and in which stage the different HFs are in at the onset of the deregulation, different HC stages or HF types may be affected. As a consequence, either anagen induction, anagen promotion or cytodifferentiation, catagen induction, catagen promotion, telogen induction or telogen promotion or several of these stages are impaired and the HC disturbance may affect all or only some HF types.…”
Section: Hair Cycle Disturbance/arrestmentioning
confidence: 99%